ANALYSIS OF THE CURRENT STATE OF UNEMPLOYMENT IN SOCIETY - Bolortsetseg Sumiya; Erdenechimeg Bor (International Journal of Innovative Technologies in Social Science, 2025)
The aim of this study is to examine the current unemployment situation in Mongolian society and assess its effects on social security. By 2024, the unemployment rate in Mongolia had reached 5.2%, negatively impacting social stability and serving as a key obstacle to economic growth.The research drew on data from the National Statistics Committee, research materials, and the findings of the labor market demand barometer survey. Employing a systems approach methodology, the study analyzed unemployment and identified its challenges and implications for social security.Findings revealed that out of Mongolia's 2.1 million individuals aged 15 and above, 1.2 million are part of the labor force, while 877,000 are not. Women make up 54.5% of registered unemployed individuals, with men comprising 45.5%. Notably, the unemployment rate is higher among young people aged 15-24 compared to other age brackets.The primary factors contributing to unemployment include skill mismatches, challenges in transitioning from education to employment, systemic issues, and a lack of needs-based approaches. Additionally, issues such as labor market imbalances, low wages, and a significant rate of informal employment (24.3%) further exacerbate the problem.Unemployment leads to adverse outcomes like decreased income, poverty, social exclusion, crime, and emotional strain, impacting social security directly. The research suggests the necessity of implementing holistic strategies to address unemployment and boost employment rates.